2015
DOI: 10.1007/s12253-015-9964-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Histological and non-Invasive Methods for the Detection of Liver Fibrosis: The Values of Histological and Digital Morphometric Analysis, Liver Stiffness Measurement and APRI Score

Abstract: Prognosis and treatment of liver diseases mainly depend on the precise evaluation of the fibrosis. Comparisons were made between the results of Metavir fibrosis scores and digital morphometric analyses (DMA), liver stiffness (LS) values and aminotransferase-platelet ratio (APRI) scores, respectively. Liver biopsy specimens stained with Sirius red and analysed by morphometry, LS and APRI measurements were taken from 96 patients with chronic liver diseases (56 cases of viral hepatitis, 22 cases of autoimmune- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In addition, research reported that up-regulation of lncRNA H19 significantly promotes epithelial to mesenchymal transition (EMT) progression and accelerates colorectal cancer cell growth by competing binding the miR-138 and miR-200a to modulate the derepression of targeted genes Vimentin, ZEB1, and ZEB2[ 24 ]. Peng et al found lncRNA ROR can mediate the expression of miR-145 and participated in proliferation, migration and invasion of colon cancer cell[ 25 ]. Recent studies have revealed that the lncRNA PART-1 was up-regulated in colorectal cancer, functioned as a competitive endogenous RNA to regulate the targeted gene DNMT3A by sponging miR-143, participated in colorectal cancer cell proliferation and metastasis[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research reported that up-regulation of lncRNA H19 significantly promotes epithelial to mesenchymal transition (EMT) progression and accelerates colorectal cancer cell growth by competing binding the miR-138 and miR-200a to modulate the derepression of targeted genes Vimentin, ZEB1, and ZEB2[ 24 ]. Peng et al found lncRNA ROR can mediate the expression of miR-145 and participated in proliferation, migration and invasion of colon cancer cell[ 25 ]. Recent studies have revealed that the lncRNA PART-1 was up-regulated in colorectal cancer, functioned as a competitive endogenous RNA to regulate the targeted gene DNMT3A by sponging miR-143, participated in colorectal cancer cell proliferation and metastasis[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The invasive nature of this test and the potential risks associated have driven the search of a noninvasive method for diagnosis and follow up of IFALD. The APRI has been validated to grade liver fibrosis in adult patients with chronic viral hepatitis 12 16 …”
Section: Introductionmentioning
confidence: 99%
“…TE proved also to be more accurate than APRI score in study published by Halasz et al[ 71 ] including 22 cases of AIH.…”
Section: Ultrasound Imagingmentioning
confidence: 91%